Effect of chitosan and Pediococcus acidilactici on E. coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes in meatballs - Incili, Gokhan Kursad; Karatepe, Pinar; Ilhak, Osman Irfan (Elsevier, 2020)
The aim of this study was to determine the single and combined effect of chitosan and Pediococcus acidiiactici (B-LC-20) on Escherichia coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes in meatballs. After spiking the samples with pathogens, meatball mixture was divided into 4 groups as control, chitosan, B-LC-20 and chitosan + B-LC-20. Subsequently, chitosan (0.4%) and P. acidilactici (6.73 log(10)) was added into the treatment groups. P. acidilactici effectively decreased the numbers of E. coli O157:H7 in B-LC-20 group in 10 days (P < 0.05). The differences in L. monocytogenes count on day 0, between the control (6.8 log(10)) and chitosan + B-LC-20 (5.3 log(10)) groups were found to be significant (P < 0.05). During the storage period; total mesophilic aerobic bacteria (TMAB), Lactobacillus-Leuconostoc-Pediococcus (LLP) and yeast-mold counts in control group were higher than the chitosan and chitosan + B-LC-20 (P < 0.05). Briefly, chitosan was found to be effective on E. coli O157:H7 and L. monocytogenes. In addition, P. acidilacitici showed an inhibitory effect on E. coli O157:H7. The combination of chitosan and P. acidilactici exhibited a slight inhibitory effect on E. coli O157:H7 and L monocytogenes. It is concluded that the studies on bio-protective cultures combined with chitosan, could be optimized and used for food safety.
Keywords: Chitosan; E. coli O157:H7; Listeria monocytogenes, meatballs; Pediococcus acidilactici